Mean Platelet Volume and Gestational Diabetes Mellitus: A Systematic Review and Meta-Analysis - Zhongwei Zhou; Hongmei Chen; Mingzhong Sun; Huixiang Ju (Journal of Diabetes Research)
Aim. To evaluate the association between mean platelet volume (MPV) and gestational diabetes mellitus (GDM). Methods. A systematic literature search was performed in PubMed, EMBASE, Web of Science, and The Cochrane Library up to 4 September 2017. Pooled standardized mean differences (SMD) and 95% confidence interval (CI) were calculated using a random-effect model. Results. Nineteen studies comprising 1361 GDM patients and 1911 normal pregnant women were included. MPV was increased in GDM patients when compared with healthy pregnant women (SMD: 0.79; 95% CI: 0.43–1.16; P<0.001). Subgroup analyses revealed that such trend was consistent in the third-trimester (SMD: 1.35; 95% CI: 0.72–1.98), Turkish (SMD: 0.81; 95% CI: 0.43–1.19), and Italian (SMD: 2.78; 95% CI: 2.22–3.34) patients with GDM and the patients diagnosed based on Carpenter and Coustan criteria (SMD: 1.04; 95% CI: 0.42–1.65). Significantly higher MPV also were observed within cross-sectional studies (SMD: 0.99; 95% CI: 0.49–1.49). Remarkable between-study heterogeneity and potential publication bias were observed in this meta-analysis; however, sensitivity analysis indicated that the results were not unduly influenced by any single study. Conclusions. GDM patients are accompanied by increased MPV, strengthening the clinical evidence that MPV may be a predictive marker for GDM.